Software Testing. - Bryce, Renee; Kuhn, Rick (Computer (00189162), 2014)
Ensuring software's reliability and effectiveness--particularly as its role in society becomes ubiquitous, and the platforms on which it operates continue to evolve--is increasingly critical, ever more challenging, and replete with moving targets.